Occasional Tillage in a Wheat-Sorghum-Fallow Rotation - John Holman; Augustine Obour; Lucas Haag (Kansas Agricultural Experiment Station Research Reports, 2025)
Beginning in 2012, research was conducted near Garden City and Tribune, KS, to determine the effect of a single tillage operation every 3 years on grain yields in a wheat-sorghum-fallow (WSF) rotation. Treatments included no-till, single tillage post wheat harvest in mid-August, and single tillage in mid-June during the fallow phase. This study was revised with the addition of two more intensive tillage treatments since 2019. The two additional treatments were 1) two tillage operations during the fallow phase, and 2) one tillage during fallow phase and one tillage post wheat harvest. Grain yield varied greatly by year and location. Wheat yields ranged across years from mid-20s to 90 bu/a at Tribune and less than 10 to 100 bu/a at Garden City. Grain sorghum yields ranged from 40 to greater than 140 bu/a, depending upon year and location. Drought and hail at Garden City resulted in several years of no harvestable grain sorghum at Garden City. Wheat yields were greater when tillage occurred during the fallow phase at Garden City. There were no differences in wheat yield at Hays or Tribune. Grain sorghum yield was greater in no-till at Tribune. There were no differences in grain sorghum yield at Garden City or Hays. There are some year-by-treatment differences, and treatment differences might be increasing over time. For these reasons, more years of data are needed. Currently, this study supports the hypothesis that if herbicide-resistant weed populations are a challenge, an occasional tillage operation will have little effect on crop yield.
Keywords: No-till; herbicide resistant weeds; crop rotation